359 AMG 757, a half-life extended bispecific T-cell engager (BiTE®) immune therapy against DLL3 in SCLC: phase 1 interim results. (9th November 2020) - Borghaei, Hossein; Boyer, Michael; Johnson, Melissa; Govindan, Ramaswamy; Rodrigues, Luis Paz-Ares; Blackhall, Fiona; Boosman, Rene; Champiat, Stéphane; Hummel, Horst-Dieter; Victoria Lai, W; Udagawa, Hibiki; Chiang, Anne; et al.
Abstract : Background: Delta-like ligand 3 (DLL3) is an inhibitory Notch ligand that is highly expressed in small cell lung cancer (SCLC) and minimally expressed in normal tissues. 1 AMG 757, a half-life extended BiTE® immune therapy, binds to DLL3 on tumor cells and CD3 on T cells, resulting in T cell-dependent killing of tumor cells. We report initial safety and efficacy from the ongoing phase 1 study of AMG 757 in patients with SCLC. Methods: AMG 757 was administered intravenously every two weeks (with/without step dose) at doses of 0.003–3.0 mg. Eligible patients had SCLC that progressed or recurred following ≥1 platinum-based regimen. Antitumor activity was assessed using modified RECIST 1.1. The study was approved by the Ethics Board at participating institutions. Results: As of 1 June 2020, safety and efficacy data are available for 31 patients enrolled at the first seven dose levels (DL) with median age, 63 (44–74) years; ECOG PS: 0–1, n=30 (96.8%); median prior lines, 2.0 (1–6); and previous PD-1/PD-L1 treatment: n=12 (38.7%). Median treatment duration was 6.1 (0.1–59.4) weeks. Treatment-emergent adverse events (AEs) were reported for 30 (96.8%) patients. AMG 757-related AEs occurred in 25 (80.6%) patients, including 5 (16.1%) that were grade ≥3 and one (3.2%) grade 5 (pneumonitis in DL5 [0.3 mg]). Three AEs (dyspnea, pneumonitis, fatigue) led to treatment discontinuation. The most common AE was cytokine release syndrome (CRS), which was reported in 11 (35.5%) patients. CRS AEs were grade 1–2, consisted mainly of fever with/without hypotension, and occurred mostly within 24 hours of the first or second dose of AMG 757. CRS events were reversible, did not lead to treatment interruption or discontinuation, and were managed with supportive care, corticosteroids, and/or anti-IL 6 therapy. The MTD for AMG 757 has not yet been reached. AMG 757 exhibited dose proportional increase in exposures. Response to AMG 757 is shown (figure 1). Confirmed partial response was reported in 5 (16.1%) patients (1/12 [8.3%] in DL5, 1/8 [12.5%] in DL6, 3/7 [42.9%] in DL7), and stable disease in 8 (25.8%) of all treated patients. Most responses occurred after 8 weeks on treatment. All responders remain on treatment with duration of response ranging from 2.0+ to 7.4 months+. Conclusions: AMG 757 administered at a dose of up to 3 mg every two weeks has an acceptable safety profile and shows anti-tumor activity in patients with relapsed/refractory SCLC. Further dose escalation is ongoing. Trial Registration: NCT03319940 Ethics Approval: The study was approved by the Ethics Board at participating institutions. Consent: N/A Reference: Leonetti A, Facchinetti F, Minari R, Cortellini A, Rolfo CD, Giovannetti E, Tiseo M. Cell Oncol (Dordr). 2019;42:261–273.